The utilization of SiNWs/AuNPs-modified indium tin oxide (ITO) in fabrication of electrochemical DNA sensor - Abdul Rashid, Jahwarhar Izuan; Yusof, Nor Azah; Abdullah, Jaafar; Hashim, Uda; Hajian, Reza (Elsevier, 2014)
This work describes the incorporation of SiNWs/AuNPs composite as a sensing material for DNA detection on indium tin-oxide (ITO) coated glass slide. The morphology of SiNWs/AuNPs composite as the modifier layer on ITO was studied by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). The morphological studies clearly showed that SiNWs were successfully decorated with 20 nm-AuNPs using self-assembly monolayer (SAM) technique. The effective surface area for SiNWs/AuNPs-modified ITO enhanced about 10 times compared with bare ITO electrode. SiNWs/AuNPs nanocomposite was further explored as a matrix for DNA probe immobilization in detection of dengue virus as a bio-sensing model to evaluate its performance in electrochemical sensors. The hybridization of complementary DNA was monitored by differential pulse voltammetry (DPV) using methylene blue (MB) as the redox indicator. The fabricated biosensor was able to discriminate significantly complementary, non-complementary and single-base mismatch oligonucleotides. The electrochemical biosensor was sensitive to target DNA related to dengue virus in the range of 9.0–178.0 ng/ml with detection limit of 3.5 ng/ml. In addition, SiNWs/AuNPs-modified ITO, regenerated up to 8 times and its stability was up to 10 weeks at 4 °C in silica gel.